Surface Quality Comparison of Down and Up cut Technique on CNC Milling Machine toward ST-37 Steel Material - Eko Indrawan; Yufrizal A; Rifelino Rifelino; Rahmad Fajri Ula Agus Herianto (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2020)
The purpose of this research is comparing down and up cut technique on milling process toward ST-37 steel material by using HSS Ø12 mm end mill cutter. The surface roughness result of down cut technique is achieved Ra 2.39 μm which is equivalent to N7 roughness level at lowest cutting speed 20 m/mnt. Moreover, the highest roughness Ra 3.61 μm obtained at highest cutting speed 30 m/mnt which is equivalent to N8 roughness level. While, the quality of up cut technique yield the roughnes Ra 3.94 μm, equivalent to N8 roughness level at lowest cutting speed 20 m/minute, whilst, Ra 6.01 μm that equivalent to N9 roughness level on highest cutting speed condition 30 m/minute. The surface roughnes value achieved between N7-N9 level (ISO). Down cut technique is recommended in order to achieve good surface quality, because it could be generate lower surface roughness on material. Tujuan dari penelitian ini adalah membandingkan teknik down cut dan up cut pada proses freis terhadap material baja ST-37 dengan menggunakan end mill cutter diameter Ø12 mm. Hasil kekasaran permukaan dari teknik down cut adalah Ra 2,39 μm yang setara dengan level kekasaran N7 pada kecepatan potong terendah 20 m/mnt. Selanjutnya, kekasaran tertinggi Ra 3,61 μm diperoleh pada kecepatan potong tertiggi 30 m/mnt yang setara dengan level kekasaran N8. Sementara itu, kualitas teknik up cut menghasilkan kekasaran Ra 3,94 μm yang setara dengan level kekasaran N8 pada kecepatan potong terendah 20 m/mnt, sedangkan Ra 6,01 μm yang setara dengan level N9 pada kecepatan potong tertinggi 30 m/mnt. Harga kekasaran permukaan material diperoleh di antara level N7-N9 (nomor kekasaran ISO). Teknik down cut direkomendasikan untuk memperoleh kualitas permukaan yang baik, karena teknik ini dapat menghasilkan kekasaran permukaan yang lebih rendah pada benda kerja.